Synthesis of (2-amino)ethyl derivatives of quercetin 3-O-methyl ether and their antioxidant and neuroprotective effects - Lee, Young Hun; Kim, Hyoung Ja; Yoo, Ho; Jung, Seo Yun; Kwon, Bong Jin; Kim, Nam-Jung; Jin, Changbae; Lee, Yong Sup (PERGAMON-ELSEVIER SCIENCE LTD, 2015)
Reactive oxygen species have been implicated in several diseases, particularly in ischemia-reperfusion injury. Quercetin 3-O-methyl ether has been reported to show potent antioxidant and neuroprotective activity against neuronal damage induced by reactive oxygen species. Several aminoethyl-substituted derivatives of quercetin 3-O-methyl ether have been synthesized to increase water solubility while retaining antioxidant and neuroprotective activity. Among such derivatives, compound 3a shows potent and well-balanced antioxidant activity in three types of cell-free assay systems and has in vivo neuroprotective effects on transient focal ischemic injury induced by the occlusion of the middle cerebral artery in rats. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: MOLECULAR-MECHANISMS; PEROXIDATION; FLAVONOIDS; ISCHEMIA; DISEASE